Analisis Efisiensi Tata Letak Gudang Di Bossfood Medan - Simanjuntak, Rizka A; Ermawati, Devy; Napitu, Regina F.G; Nasution, Wulan F.A.I; Novita, Vivianti (Institut Agama Islam Yasni Bungo Jambi, Indonesia, 2024)
This study aims to analyze the efficiency of the warehouse’s layout at Bossfood Medan, a company operating in the food industry. With the increasing market demand, warehouse layout becomes a critical element impacting productivity, space optimization, and operational cost reduction. This research adopts a qualitative approach using observation and interviews, with primary data obtained from the warehouse manager of Bossfood Medan. The findings reveal that the implemented warehouse layout, including the use of the FIFO (First In First Out) method and cross-docking processes, supports operational efficiency. However, there are challenges related to limited human resources, Which hinder smooth operations, especially in tasks such as stock-taking. The current outsourcing system is also not fully effective in meeting the warehouse labor needs. Based on these findings, the study concludes that the warehouse layout of Bossfood Medan is relatively efficient but requires improvements in human resource management and technology adoption. Recommendations include hiring additional staff, implementing a technology-based warehouse management system, and conducting regular evaluations of the layout to support the company’s growth in the future.